Bone adaptation under mechanical influence: Regional differences in bone mineral density, degree of mineralisation, micro-architecture evaluated by pQCT, BSE imaging and microCT - Lai, Yau Ming (ProQuest Dissertations & Theses, 2006)
Bone material and structural properties should be considered in the evaluation of bone adaptation to mechanical influences. The conventional densitometry provides only a projectional and scalar measurement of bone mineral density (BMD). Thus, it does not allow separate measurement of cortical and trabecular bone and differentiate regional changes in bone qualities. A model comprising of both human subjects and cadavers was employed to investigate the long bone regional adaptation under habitual loading using different imaging modalities. It is hypothesized that there is differential regional bone adaptation in response to strain magnitude/mode. Peripheral quantitative computed tomography (pQCT) measurement in postmenopausal women showed significant regional variations of cortical bone mineral density (cBMD) and trabecular bone mineral density (tBMD) in the distal tibia and distal radius. The higher cBMD and tBMD were related to its prevalent compressive stress during habitual loading. Circularly polarized light (CPL) microscopy supported this by showing a preferred transverse to oblique collagen fibre orientation in the compression cortices. The higher tBMD associated with greater micro-architecture parameters as measured by micro-computed tomography (microCT). Backscattered electron (BSE) imaging study of osteon morphometry and degree of mineralisation in the cadaveric distal tibia and radius showed that the variation of cBMD was due to differences in intracortical porosity (IP) rather than to the variation of mineralisation. Distal tibia had significantly lower cBMD than the distal radius. This lower cBMD was compensated by having greater cortical thickness, polar moment of inertia, and preferred collagen fibre orientation. The tibia, being subject to habitual dynamic compressive loading as compared to the nonweightbearing nature of the radius, may activate a higher remodelling rate, which does not allow full secondary mineralisation. This was evidenced in the study by showing lower cBMD and greater IP. The compensatory increase in bone geometry aims to withstand the sustained bend and torsion loading in this region. In summary, compressive loading is more osteogenic bringing about greater regional BMD and alteration of bone micro-architecture. Design of exercise intervention to enhance bone quantity and quality should consider the strain mode effect. Compensation between the material density and structure is evidenced which allows bone strengthening. Regional bone adaptation as revealed by multiple imaging modalities allows better understanding of changes at different levels of bone organization.